A large deletion in the human alpha-globin cluster caused by a replication error is associated with an unexpectedly mild phenotype. - Rugless, M; Fisher, C; Old, J; Sloane-Stanley, J; Ayyub, H; Higgs, D; Garrick, D (2008)
We have characterized a newly identified 16.6 kb deletion which removes a significant proportion of the human alpha-globin cluster including the psizeta1, alpha(D), psialpha1 and alpha2-globin genes but leaves the duplicated alpha1 gene intact. This complicated rearrangement results from a combination of slippage and strand switching at sites of microhomology during replication. Functional analysis shows that expression of the remaining alpha1 gene is increased, rather than down-regulated by this deletion. This could be related to its proximity to the remote upstream alpha-globin regulatory elements or reduced competition for these elements in the absence of the dominant alpha2-globin gene. The finding of a very mild phenotype associated with such an extensive deletion in the alpha-globin cluster implies that much of the DNA removed by the deletion is likely to be functionally unimportant. These findings suggest that other than the upstream regulatory elements and promoter proximal elements there are unlikely to be additional positive cis-acting sequences in the alpha-globin cluster.